Intravaginal Foreign Body: A Rare Cause of Persistent Vaginal Discharge in a Child - Ndeye Fatou Seck; Florent Tshibwid A. Zeng; Ndeye Aby Ndoye; Gabriel Ngom (Wolters Kluwer Medknow Publications, 2024)
Vaginal discharge is a common gynaecologic complaint in pre-menarchal girls. However, an intravaginal foreign body (FB) must be suspected when it is persistent. We report the case of a referred 4-year-old girl with a 5-month history of persistent foul-smelling vaginal discharge. Clinical examination confirmed purulent vaginal discharge, along with a vaginal granuloma. A hard, intravaginal object was felt through the anterior rectal wall on digital rectal examination. A plain pelvic X-ray revealed a radiopaque object whose intravaginal position was confirmed by ultrasonography. The patient underwent granuloma excision plus FB removal and antibiotic treatment. The 12-month follow-up was unremarkable.